The Effect of Regulation Projects on the Water and Sediment Dynamic in Bifurcation Estuaries. (2015) - Yun, Pan; Xiping, Dou; Xiangyu, Gao; Zengxiang, Jiao; Lei, Ding
Abstract: Estuary connecting links between river and ocean, and is also departure point and destination of sea transport. Because of depth of natural estuarine channel often unable meet the demand of shipping, regulation and dredging must be carried on waterway. But the mechanism of regulation projects affecting branching estuaries is not definitely clear. Uniform flow is used to validate an established bifurcation estuary model to determine effects of one branch on the other branch and the response of water-sediment dynamic been subject to regulation projects. The research results show that the change is unequal between section discharge and section sediment flux. There exists the optimum dike length that ensure the discharge and sediment flux are less influenced by dikes. The appropriate relative length is 0.62 and the extreme relative length is 0.78 through regression analyzing. The section discharge ratio is consistent under action of uniform flow and tide. The section sediment flux ratio about 0.5 is different between uniform flow and tidal cases. The research results can provide references for managing of bifurcation estuaries and further researching.